Fluorescent detection of point mutation via ligase reaction assisted by quantum dots and magnetic nanoparticle-based probes. Issue 41 (12th May 2017) - Heidari Sharafdarkolaei, S.; Motovali-Bashi, M.; Gill, P.
Abstract : A nanodiagnostic genotyping method was presented for point mutation detection directly in human genomic DNA based on ligase reaction coupled with quantum dots and magnetic nanoparticle-based probes. Abstract : A nanodiagnostic genotyping method was presented for point mutation detection directly in human genomic DNA based on ligase reaction coupled with quantum dots and magnetic nanoparticle-based probes. For this purpose, allele-specific probes, including a biotin-labeled common probe and two biotin-labeled allele-specific probes were designed for mutant and wild alleles of human beta globin gene (IVS-II-I G → A point mutation). When genomic DNA carried the mutation site, the common probe and allele-specific probe were ligated to form exponential amplified biotin-labeled fluorescence ligation products. These ligated products were captured by streptavidin-coated magnetic nanoparticles at one end and then attached to a QD 605-streptavidin conjugate at the other end to be detected fluorescently. Thereafter, the genotypes were identified conveniently according to the fluorescence color of quantum dots using a rotor-gene 6000Q real-time rotary analyzer. The results demonstrated the sensitivity and specificity percentages of this nanomolecular mutation detection method were 85.45% and 95.77% respectively. In addition, this method could be a high throughput and high sensitivity detection system that represents suitable non-PCR based nanodiagnostics for detection of other point mutations.